PENGARUH PELATIHAN PASTRY & BAKERY SECARA ONLINE TERHADAP MINAT KEWIRAUSAHAAN - Nurul Sukma Lestari; Sintani Sintani; Safiatur Rokhmah; Hana Desy Natalina (Universitas Muhammadiyah Tangerang, 2023)
This study aims to determine the effect of online pastry & bakery training on entrepreneurial interest during pandemic era. The research method used is quantitative, using SPSS software for data processing. The sample used in this study were 105 respondents who had attended online training on making pastries and bread. Data was collected through a questionnaire made in the form of a google form and shared online. Researchers will select respondents that are domiciled only in the territory of Indonesia with the object of research being shown to Indonesian people who have attended online pastry and bakery training during the Covid-19 pandemic. Through the linear regression test, the results showed a significant influence between online pastry and bakery training on entrepreneurial interest. This supports several previous studies that have been conducted by other researchers. The limitation of this study is a small number of samples and only limited to pastry and bakery online training. This research can be useful for the wider community so that it can generate intentions to entrepreneurship and attending training is a way to be able to enrich the knowledge needed in entrepreneurship.